THERMODYNAMICS OF A CHALCONE-BASED POLYMER BY INVERSE GAS CHROMATOGRAPHY METHOD - Adiguzel, Aysegul C.; Korkmaz, Burak; Cakar, Fatih; Cankurtaran, Ozlem; Hepuzer Gursel, Yesim; Senkal, Bahire Filiz; Karaman, Ferdane (YILDIZ TECHNICAL UNIV, 2020)
In this study, an inverse gas chromatography (IGC) study of thermodynamic interactions of a chalcone modified poly (styrene) based polymer (PVBC-DMAC) with some solvents was presented. For this purpose, the retention data of carefully selected polar and non-polar solvents on PVBC-DMAC was obtained by IGC instrument at temperatures between 358.2 K and 383.2 K. Then, the polymer-solvent interaction parameters for Flory-Huggins theory, chi(infinity)(12) and the equation of state theory, chi(12)*, the effective exchange energy parameters, X-eff, the weight fraction activity coefficient, Omega(infinity)(1), and also the partial molar heat of mixing at infinite dilution of solvent, Delta(H) over bar (infinity)(1), the molar heat of vaporization of solvent, Delta(H) over bar (nu), and the partial molar heat of sorption of solvent, Delta(H) over bar (s)(1) were calculated. The obtained results were discussed.
Keywords: Inverse gas chromatography; thermodynamics; poly (styrene) based polymer; SOLUBILITY PARAMETERS; ETHER IMIDE; PHOTOPOLYMER; BLENDS; Engineering